2014
DOI: 10.1016/j.ijindorg.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Indirect network effects and the quality dimension: A look at the gaming industry

Abstract: a b s t r a c t JEL classification: L14 L82 M21 Keywords: Network effects Superstar software Game console Killer applicationsTwo-sided markets consist of platforms that need to bring both retail consumers and complementary goods producers on board to be successful. Consumer adoption of these platforms can often hinge on the presence and magnitude of indirect network effects -the positive feedback loop where a larger base of adopters of a primary product ("hardware") creates a larger market for complementary go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This organizational learning influences innovation and performance [53]. The quality of complementary goods influences the strength of the indirect network effects on consumers' platform adoption [54] and is deemed by consumers to reflect the quality of the platform [55]. Thus, platform providers need complementors that have gained experience drawn from organizational learning in the market and that can develop superior complementary goods.…”
Section: Possible Influencial Factors On Complementors' Competitive Omentioning
confidence: 99%
“…This organizational learning influences innovation and performance [53]. The quality of complementary goods influences the strength of the indirect network effects on consumers' platform adoption [54] and is deemed by consumers to reflect the quality of the platform [55]. Thus, platform providers need complementors that have gained experience drawn from organizational learning in the market and that can develop superior complementary goods.…”
Section: Possible Influencial Factors On Complementors' Competitive Omentioning
confidence: 99%
“…Recent studies have criticized earlier research that examined demand-side effects without controlling for the endogeneity of title availability (e.g., Dubé, Hitsch & Chintagunta, 2010;Gretz, 2010;Inceoglu & Park, 2011;Zhu & Iansiti, 2012;Kim, Prince & Qiu, 2014). In a reanalysis of the data from nine consumer electronic product categories, Stremersch et al (2007) compared the relative importance of the supply and demand effects.…”
Section: Attributes Of Ine Softwarementioning
confidence: 99%
“…They concluded that software availability typically followed hardware sales, while 'the reverse almost never happens' (Stremersch et al, 2007, p. 68). However, more recent studies focusing on specific categories have found evidence supporting the existence of demand effects in the markets for home video games (e.g., Corts & Lederman, 2009;Dubé, Hitsch & Chintagunta, 2010;Gretz, 2010;Zhu & Iansiti, 2012;Kim, Prince & Qiu, 2014) and DVD players (e.g., Inceoglu & Park, 2011).…”
Section: Attributes Of Ine Softwarementioning
confidence: 99%
See 2 more Smart Citations